PEMETAAN DAERAH RAWAN KEBAKARAN HUTAN DAN LAHAN DI KABUPATEN ROKAN HILIR - Ikhwan, Muhammad (Fakultas Kehutanan Universitas Lancang Kuning, 2016)
Forest fire is one form of the disorder occur more frequently. The negative impact caused by forest fires large enough cover ecological damage, declining biodiversity, the decline in the economic value of forest and soil productivity, chan ges in micro and global climate and the smoke damage the health of people and disrupting transport by land, river, lake, sea and air. Given the impact of the forest fires, the efforts to protect the forest areas is very important. In an effort to control forest fires it is essential to map vulnerability to wildfires prepared to know which areas have the potential for fires. The purpose of this study was to map the vulnerability of land and forest fires in an effort to support the establishment of forest fire management strategy. Through a vulnerability map wildfires can provide vulnerability information to policy-making forest fire prevention / fire control and is expected to be the basis in prevention efforts as early as possible. The study was conducted from June until July 2014 and the case study research in Rokan Hilir Regency. Results of mapping the vulnerability of land and forest fires shows that most areas of Rokan Hilir Regency has a severe impact and the level of vulnerability is very high. Low-prone areas have extensive 9152.55 hectares (1.01%), the rate of moderate-prone area of 158,943.95 hectares (17.49%), high-level-prone area of 382,448.62 hectares (42.08%) and very high levels of vulnerability with an area of 358,374.00 hectares (39.43%).